Knowledge Integration for Low Carbon Transition: The Case of Energy Retrofit - Sibilla, Maurizio; Kurul, Esra (European Journal of Sustainable Development, 2018)
The Energy Retrofit concept plays an important role in the transition to low carbon cities, because buildings make a transdisciplinary perspective. Thus, an integrated approach to research, learning and teaching in the built environment disciplines is required. The Authors present the final stage of the first work package of an H2020-Marie-Sklodowska Curie project, which focuses on the development of an Innovative Learning Platform for Knowledge Integration in Energy Retrofit. This paper, which first summarizes the conceptual framework that was elaborated in an earlier phase, focuses on the methodological approach that was used to define the relevant information networks concerning Energy Retrofit using a cognitive mapping technique. The methodology is applied to 10 case studies in order to explore the relationships between Energy Retrofit and built environment transformation processes. The methodological approach is structured as follows: 1) Collecting case studies; 2) Identifying main topics; 3) Coding list of concepts; 4) Defining relationships; and 5) Updating the conceptual framework. The findings show that the adopted methodological approach is useful for integrating diverse disciplinary perspectives and for improving users’ cognitive skills that are involved in mutual and joint learning processes. In conclusion, this study presents an innovative approach to research, learning and teaching in built environment disciplines. Keywords: Energy Retrofit; Built Environment; Integrated Project; Knowledge Integration; Design Education